Routing of Cargo Vehicles by Multi-Factor Simulation - Luiz Pinto da Silva, Deividi; Mello, Braulio (iSys - Journal of Information Systems, 2024)
The effectiveness of supply chain systems depends on the quality of the logistic strategies. The vehicle routing problem is one of the important ones in this context. Traditional solutions of routing use to combine distance and time to define a route. However, there are additional and relevant aspects, or factors, to improve the routing effectiveness. For instance: timing windows of stops; routing vs tracing; velocity according to the truckload type; and road quality. Traditional solutions do not allow flexible and configurable sets of factors for the routing process. This work introduces a new Modeling and Simulation solution to combine multi factors for the routing process. The proposed model allows configuring multi properties according to the truckload features. As results, the model identifies the route with the best balance among the configured property requirements.